The Influence of Leadership Style and Job Insecurity on Turnover Intention PT. Hoffmen Energi Perkasa - Putri, Ice Tribuana; Supriaddin, Nofal; Sabilalo, Mahmuddin A. (International Journal of Management and Education in Human Development, 2024)
The aim of this research is to test and explain the influence of leadership style and job insecurity on turnover intention at PT. Hoffmen Energi Perkasa. This research approach is a survey with an explanatory research design. Data collection was carried out using a survey method using an instrument in the form of a questionnaire. The population of this research is all employees of PT. Hoffmen Energi Perkasa, totaling 219 people. The sample was determined using the Slovin formula with a precision of 10%, resulting in a total sample of 69 people. The analysis equipment used is Partial Least Squares (PLS) Analysis. The research results show that (1) Leadership Style has a significant effect on Turnover Intention. (2) Job Insecurity has a positive and significant effect on Turnover Intention. Thus, it can be concluded that changes in increasing Leadership Style and Job Insecurity have a positive and significant contribution to increasing Turnover Intention.